PLATELETS AND PLATELET-DERIVED MICROVESICLES: PHENOTYPE, CONTENT, IMPACT ON ENDOTHELIAL CELLS - Olga I. Stepanova; Marina A. Pereviazkina; Markova L. Kseniia; Sergey A. Selkov; Dmitriy I. Sokolov (Медицинская иммунология, 2019)
Platelets are circulating anucleated structures derived from megakaryocytes. Intercellular adhesion molecules, Toll-like receptors, chemokine and cytokine receptors are represented on their surface. Platelets contain biologically active molecules, including chemokines, cytokines, and growth factors. Due to its cytological features (membrane system and secretory granules), platelets are capable of fast activating and interacting with other cells. Platelets are involved in hemostasis, immune reactions, and angiogenesis.  Platelets can be activated by components of subendothelium, complement system proteins, products of secretion of other platelets. Activation process is mediated through calcium. When activated, platelets change their morphology, release secretory granules and produce microvesicles – a relatively new target of biological research.  The aim of this review is a comparative description of platelets and their microvesicles. Platelet-derived microvesicles perform platelets functions and communicate with other cells, including endothelial cells. Microvesicles is a promising object of research, and the possibility of their use as a diagnostic and therapeutic agent is being actively studied. Majority of circulating microvesicles has platelet origin. Platelet-derived microvesicles contain cytokines and other proteins, lipids and nucleic acids (DNA, mRNA, microRNA). Microvesicles has  the surface markers of the parent cells; phosphatidylserine is represented on their membrane, which additionally participates in clotting due to accumulation of coagulation factors. Under the influence of microenvironment signals, the composition, phenotype of platelet microvesicles, as well as their functional abilities towards the endothelium may vary depending on the stimulus. The effect they have on angiogenesis and regeneration has not been sufficiently elucidated, experimental data demonstrate controversial effects. In pathologies accompanied by endothelial dysfunction an increase in the level of platelet microvesicles is observed, which indicates their possible participation in the pathogenesis. The effect of platelets and their MV on the endothelium, including activation of various signaling pathways in the endothelium, remains the subject of further research.